ENDOMETRIOSIS AND ENDOMETRIOID CANCER OF THE OVARIES: WHAT IS COMMON TO THEM? - M. M. Sonova (ABV-press, 2014)
Genital endometriosis and reproductive system tumors have the similar mechanisms of development, such as invasion, growth, metas- tasis, diminished apoptosis, and aromatase expression. Despite these similarities, endometriosis is not referred to as malignancy. According to the data available in the literature, the described cases of malignization of endometriosis foci are as high as 5%. This phe- nomenon is of interest not only from the oncological, but also biological standpoint.